Comparison of success rate and time to obtain venous cannulation by cutdown technique at 3 locations using canine cadavers. Issue 3 (2nd February 2022) - Jones, Nadine; Handel, Ian G.; Llewellyn, Efa
Abstract: Objective: To compare the success rates and time taken to cannulate the jugular, cephalic, and lateral saphenous veins using a cutdown technique by personnel with 4 different levels of experience. Design: Prospective ex vivo study. Setting: Veterinary university teaching hospital. Animals: Eighteen canine cadavers. Interventions: Recently euthanized canine patients that were donated to the hospital for research purposes between October 2019 and March 2020 were enrolled. Four groups of personnel participated in the study to give 4 varying levels of experience: 8 final year veterinary students, 2 registered veterinary nurses, 1 emergency and critical care intern and 1 ACVECC diplomate. Each cannula placer had 5 minutes to attempt cannulation by venous cutdown at each site. Time to venous cannulation (VC) was compared for each site and group and complications encountered during each attempt recorded. Measurements and Main Results: The overall success rate for cannulation of the jugular, cephalic, and lateral saphenous veins were 81%, 84%, and 87%, respectively. The median times for venous cutdown for all personnel were as follows: jugular vein 119 s (range 51–280 s), cephalic vein 82 s (range 39–291 s), and lateral saphenous vein 110 s (range 41–294 s). There was no difference in time to VC between veins. When comparing personnel at the 3 cannulation sites, the ACVECC diplomate was faster than the registered veterinary nurses and students ( P  = 0.042 and P  = 0.048, respectively). No differences were found between any other groups. Complications encountered often related to cadaver factors such as hematoma from antemortem venipuncture. Conclusions: All groups were able to perform venous cutdown at each site with good overall success even without prior experience of the technique. VC by cutdown technique of the jugular, cephalic, or lateral saphenous veins may be considered in an emergency setting by personnel of various skill levels.